Estrutura genética de amostras de mandacaru usando locos heterólogos de microssatélites - Fernandes, Vanessa Neves de Azevedo (2013)
Cereus is an ornamental cactus, popularly called "mandacaru" in Brazil, cultivated in gardens and in biological preservation areas. The species is ecologically, economically and industrially important due to the great variety of compounds it produces. This current research estimates the transferability of microsatellite markers of other cactus species to "mandacaru" and analyzes the specie's genetic variability establishing a relation of similarity or divergence between different samples grown in regions Northeast, South, Southeast and Central of Brazil. Thirty-three pairs of primers developed from different cactus species were evaluated for characterized the microsatellite markers. From the evaluation were selected ten pairs of primers developed from Polaskia chichipe, Ariocarpus bravoanus and Echinocactus grusonii giving a 30.30% transferability of these primers to "mandacaru'. Two of the microsatellites provided information for 2 loci, by this way were evaluated 12 microsatellite heterologous loci in 21 "mandacaru" samples. The polymorphism for the 21 samples reached 58,33%, evaluated loci showed 31 alleles at an average of 2.58 alleles per locus. Analysis of genotype frequency suggests a segregation distortion for 68 loci in which their frequency failed to present a Hardy-Weinberg equilibrium distribution. The average Fis value rate (0.0407) indicated a deficit of heterozygotes for the loci under analysis. Differential frequency of certain alleles in the different samples produced high genetic divergence (Fst = 0.4914) among them. Analyzes revealed greater genetic diversity between samples than within them, corroborating the intermediate gene flow (Nm = 0.2588). The relations of similarity and dissimilarity among the 21 samples ranged between 0.2249 and 0.9749, and produced a three-group dendrogram, two groups were made up from different samples collected in the state of Paraná, São Paulo, Piauí and Bahia whereas the third one was formed by samples collected in the state of Mato Grosso do Sul. The analysis provided a percentage variation between the samples of 55%, and within these 45%. The genetic relationships among individual genotypes also indicate formation of three different groups with the insulation from the group consisting for individuals from the region of Pantanal. The low values obtained for the test mantel r² = 0.06 shows that differentiation between samples is not related to the geographical distance separating. The results obtained in this study suggest a process of speciation of the genus Cereus, so the plants that grow in the four regions in analyzes are plants that may correspond to different species of the grup in the process of speciation.